2006
DOI: 10.1016/j.bandc.2005.12.007
|View full text |Cite
|
Sign up to set email alerts
|

An islet of social ability in Asperger Syndrome: Judging social attributes from faces

Abstract: We asked adults with Asperger Syndrome to judge pictorial stimuli in terms of certain social stereotypes to evaluate to what extent they have access to this type of social knowledge. Sixteen adults with Asperger Syndrome and 24 controls, matched for age and intelligence, were presented with sets of faces, bodies and objects, which had to be rated on a 7-point scale in terms of trustworthiness, attractiveness, social status, and age, or, in the case of objects, price. Despite impaired performance on two importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
7
22
1
2
Order By: Relevance
“…Our findings are consistent with previous adult studies reporting no significant differences in trustworthiness judgments between typical adults and adults with ASD [17][19]. However, there are also studies that have reported atypicalities in response to trustworthy and untrustworthy faces in adults with ASD [11], [20], [21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with previous adult studies reporting no significant differences in trustworthiness judgments between typical adults and adults with ASD [17][19]. However, there are also studies that have reported atypicalities in response to trustworthy and untrustworthy faces in adults with ASD [11], [20], [21].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies report no significant differences in trustworthiness judgments between typical adults and adults with ASD [17][19]. Other studies report that individuals with ASD significantly overrate the trustworthiness of negatively valenced faces [11], [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…This figure is consistent with the results of Baron-Cohen et al (2001), and others (e.g., White, Hill, Winston, & Frith, 2006) who have used this tool with high functioning adults. There was no significant difference in total scores on the AQ between men (M= 39.06, SD 6.5) and women (M = 39.27, SD 8.6); t(118) = -.153, p = .88.…”
Section: Adult Asd Diagnosis Survey 10supporting
confidence: 92%
“…Nor was there any difference in willingness to purchase reputation cues 2 Furthermore, an additional 2 x 2 mixed ANOVA also revealed an interaction between the effects of participant group (ASD, typical) and trustworthiness cue (faces, reputation) on trust behaviour, but unsurprisingly, given the small sample, this effect was only marginally significant, F(1, 16) = 3.42, p = .08, partial η 2 = .17. Caulfield et al, 2013;Mathersul et al, 2012;Pinkham et al, 2008;White et al, 2006) we observed a striking difference, relative to typical children, in the way that facial trustworthiness cues influenced behaviour.…”
Section: Insert Figure 2 About Herementioning
confidence: 42%
“…Perhaps surprisingly, studies have often failed to find evidence of atypical facial trustworthiness judgments in individuals (both children and adults) with ASD (Caulfield, Ewing, Avard and Rhodes, 2013;Mathersul, McDonald and Rushby, 2012;Pinkham, Hopfinger, Pelphrey, Piven and Penn, 2008;White, Hill, Winston and Frith, 2006). Despite the links to atypical amygdala fuctioning in ASD, only a few studies have reported selectively atypical (inflated) trust ratings F o r P e e r R e v i e w 3 of untrustworthy-looking faces (Adolphs et al, 2001;Couture et al, 2010;Losh et al, 2009).…”
mentioning
confidence: 99%